Indonesian international trade analysis in agricultural sector case study of natural rubber commodities exports in the ASEAN free market - IK, Riady (Anjoro: International Journal of Agriculture and Business, 2023)
Natural Rubber is one of Indonesia's leading export commodities and is also one of the largest suppliers in the global market. Rubber and processed rubber export commodities are categorized under the Harmonized System Code 40001 (HS Code 4001) more frequently referred to as HS-4001 so that it is easier to analyze related to commodity trade transactions where in the last few years since 2011 the share of Indonesian Natural Rubber exports always in the top 10 largest exporters in the world. Besides China as the largest exporter, it turns out that Thailand is Indonesia's strongest competitor as a Natural Rubber exporter in ASEAN, therefore with the implementation of the ASEAN Economic Community (AEC) policy in 2016 it is believed that there has been a change in the trade system, namely the export of various commodities including Natural Rubber in the Market. ASEAN. This study uses a descriptive method using various reference sources and secondary data where a lot of data comes from online media, namely various previous studies, online news, and data collected through official websites of government agencies or organizations both national and international. The results of this study indicate that international trade in Indonesian Natural Rubber commodities experienced a significant increase after the implementation of the AEC in 2016 compared to several previous years. It is hoped that the Indonesian government can further encourage natural rubber producers and entrepreneurs to continue to optimize the export of this commodity.